PERFORMANCE MEASUREMENT BASED ON BALANCE SCORECARD PERSPECTIVE OF SUSTAINABLE LEADERSHIP, CORPORATE GOVERNANCE AND HUMAN CAPITAL IN BANKING INDUSTRY - Eri Kusnanto (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
The purpose of this research was to testing the effect sustainable leadership, corporate governance and human capital on the measurement of company performance using the Balanced Scorecard of the banking industry. A sample of banking company employees with a questionnaire was taken and the data was collected using SEM to test the effect of each variable. Sustainable leadership, corporate governance and the impact of human capital on performance measurement is considerable using a balanced scorecard but regarding the effect of test moderation, human capital has no moderating effect on sustainable leadership and corporate governance on performance measurement. The use of samples is still limited from several banking companies. Companies must pay attention to the development of sustainable human resources to increase the value of the company. Also use sustainable leadership components and synergies components in measuring the balance scorecard.